Clinical Manifestation and Diagnosis of Cryptosporidiosis in Adult Infected with HIV - Nunung Ainur Rahmah; Ening Krisnuhoni; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2003)
Cryptosporidiosis is a rare infection caused by a coccidian parasite, Cryptosporidium, which could cause diarrhea in humans, especially those who are immunocompromised Cryptosporidiosis could cause self- limited diarrhea infection in immunocompetent hosts, but in immunocompromised hosts, especially those with AIDS, the diarrhea can be chronic and severe. To date, no known effective therapeutic agents have been identified. The following is one case report of cryptosporidiosis of a 27 year-old male admitted with chronic diarrhea since 2 months. Endoscopy of the ileum and colon showed hyperemia, erosion and edema, and biopsy was performed. Histopathological examination of ileum showed an atrophic villous and atypical degeneration. There was a number of circular cryptosporidium lining up along the surface of epithelium. There was inflammatory cell infiltration, consisting of lymphocytes, eosinophils and a few neutrophils in the lamina propria. Serological examination revealed an HIV-positive result. Keywords: Cryptosporidiosis, HIV, diarrhea